Prevalence and Predictors of Sexually Transmitted Infections Among Female Sex Workers in Rural Eastern India: A Cross-Sectional Study - Biswas, Aniruddha; Pal, Jayita; Sadhukhan, Sanjoy Kumar; Saren, Nilima; Ghosh, Manoj (International Journal of Human and Health Sciences (IJHHS), 2026)
Female sex workers (FSWs) remain a highly vulnerable population for sexually transmitted infections due to structural, behavioural, and occupational risk factors that often go unaddressed in rural settings. This study aimed to estimate the prevalence and identify the predictors of sexually transmitted diseases (STDs) among brothel-based FSWs in a rural area of eastern India, to guide targeted public health interventions. This community-based cross-sectional study was conducted among 210 brothel-based female sex workers in Matia Bazar, Basirhat, a rural area in eastern India, using simple random sampling from the Durbar Mahila Samanwaya Committee (DMSC) registry. Data were collected using a predesigned and pretested questionnaire. Our study found that 44.8% of FSWs showed symptoms of STIs or RTIs in the past year. Key predictors included a higher client load [AOR: 2.30; 95% CI: 1.24–4.30] and condom breakage during intercourse [AOR: 2.62; 95% CI: 1.02–6.75]. Although condom use with clients was reportedly universal, only 18.8% used them with cohabiting partners. Condom breakage was reported by 84.3%, yet post-exposure measures such as emergency contraception were infrequently adopted. The final model explained 21% of the variance in STI/RTI occurrence. High client load and condom failure significantly increase the risk of STI/RTI among brothel-based FSWs, underscoring the urgent need for enhanced condom use training and tailored intervention programmes. International Journal of Human and Health Sciences Vol. 10 No. 01 Jan’26 Page: 39-47